Recreational soccer and basketball improve anthropometric, body composition and health-related outcomes in overweight and obese young adults: A randomized multi-arm study - Xu, Qi; Silva, Rui Miguel; Zmijewski, Piotr; Li, Tingyu; Ma, Dong; Yang, LiuXi; Liu, GuiYang; Clemente, Filipe (Biology of Sport, 2025)
This study aimed to investigate the effects of 8-week programmes based on recreational soccer (SCG) and basketball (BCG) conditioned games compared to self-exercise (SECG) and inactive (ICG) control groups on anthropometry, body composition, resting heart rate (RHR), and blood pressure among sedentary overweight and obese men and women. The study included 90 volunteers (aged 19.8 ± 1.5 years; 45 women) who were assessed twice, before and after the intervention, for the waist circumference (WC), body mass index (BMI) and body composition (skinfold sum and %body fat), RHR and systolic (BPs) and diastolic (BPd) blood pressure. Members of the experimental groups participated in three training sessions per week, while the control groups either maintained their routines or engaged in self-regulated exercises. Time × group interactions were found for BMI ( p < 0.001; = 0.339), body fat ( p < 0.001; = 0.317), WC ( p < 0.001; = 0.429), skinfold sum ( p < 0.001; = 0.818), RHR ( p < 0.001; = 0.572), BPs ( p < 0.001 = 0.534) and BPd ( p < 0.001; = 0.633). Between-group analysis revealed greater improvements in BMI ( p < 0.05), body fat ( p < 0.05), WC ( p < 0.05), skinfold sum ( p < 0.05), RHR ( p < 0.001), and BPd ( p < 0.001) in the SCG and BCG compared to the SECG and ICG. No differences in improvements between the groups were observed. No time × group interactions were observed for sex ( p > 0.05). The results suggest that intervention programmes based on recreational games such as basketball or soccer are effective in improving anthropometric characteristics, body composition, and cardiovascular health in sedentary overweight and obese men and women, and are independent of sex. The effectiveness is greater when accompanied by a more significant reduction in energy intake. Engaging in self-controlled physical activity proved to be beneficial when compared to remaining inactive, despite changes in dietary intake.